Cavern of secrets - Park, Linda Sue (Park, Linda Sue. Wing & claw, 2018)
Determined to make it home, Raffa and his friends begin the journey across Obsidia. When Raffa comes across a luminous plant he's never seen before, his apothecary instincts tell him the plant may be the key to saving the creatures stuck in the Chancellor's grasp.